Intubation amidst COVID-19: how mask protocols and communication impact SARS-CoV-2 transmission among medical staff - Thu, Le Thi Anh; Nguyen, Tuan; Minh, Tri Nguyen; Thi, The La; Thuy, Dung Nguyen Thi; Nguyen Thien, Minh (International Journal of Infection Control, 2025)
Objective: To describe the sequence of (Severe acute respiratory syndrome corona virus 2) infection following endotracheal intubation in Coronavirus disease 2019 patients. Design: A retrospective case series study. This analysis focuses on cases involving hospital medical staff who contracted SARS-CoV-2 after performing endotracheal intubation on a COVID-19 patient on August 2, 2021, at Hoan My Thu Duc Hospital, a private hospital treating COVID-19 patients in Vietnam. The participants were 13 medical staff members involved in aerosol-generating procedures. Results: The infection spread to eight healthcare workers directly involved in emergency intubation. Five were suspected of contracting SARS-CoV-2 immediately following the emergency treatment of COVID-19 patients, and three were infected via transmission from their colleagues. The improper fit of N95 masks and failure to wear them during interpersonal communication were identified as significant risk factors. Conclusions: The research underscores the critical need for proper N95 mask fit during aerosol-generating procedures. Healthcare professionals treating COVID-19 patients must consistently use masks when communicating with colleagues, even outside of work hours, to curb the spread of SARS-CoV-2 among medical staff.